2017
DOI: 10.1111/dom.12907
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of subcutaneous glucose monitoring systems under routine environmental conditions in patients with type 1 diabetes

Abstract: We compared the sensor performance of 3 commercially available GM systems. A total of 12 patients with type 1 diabetes were included in a single-centre, open-label study in which the sensor performance of the Abbott FreeStyle libre (Abbott), Dexcom G4 Platinum (Dexcom) and Medtronic MiniMed 640G (Medtronic) systems over 12 hours was compared during mimicked real-life conditions (meals, exercise, hypo-and hyperglycaemia). Sensor performance was determined by fulfilment of ISO 15197:2013 criteria, calculating me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
115
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(136 citation statements)
references
References 22 publications
17
115
3
1
Order By: Relevance
“…Our results are in contrast to findings from a previous study by our research team, which determined the iCGM system to be accurate during exercise testing, with a MARD of 8.7AE5.9% and a Parks error grid of 100% for values in zone A [5]. Our results are in contrast to findings from a previous study by our research team, which determined the iCGM system to be accurate during exercise testing, with a MARD of 8.7AE5.9% and a Parks error grid of 100% for values in zone A [5].…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are in contrast to findings from a previous study by our research team, which determined the iCGM system to be accurate during exercise testing, with a MARD of 8.7AE5.9% and a Parks error grid of 100% for values in zone A [5]. Our results are in contrast to findings from a previous study by our research team, which determined the iCGM system to be accurate during exercise testing, with a MARD of 8.7AE5.9% and a Parks error grid of 100% for values in zone A [5].…”
Section: Discussioncontrasting
confidence: 99%
“…We found that glucose levels measured by FGM were slightly lower than those measured in venous blood (−6.5 mg/dL, 30 measurements) and those measured by CGM (−13.6 mg/dL, 1,279 measurements), and this tendency was similar to the results of earlier studies. Aberer et al .…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, 75-g OGTT resulted in a slower rise in glucose level as determined by FGM than that obtained by the perchloric acid hexokinase method, POC testing, test strip, and conventional CGM during the first 45-60 minutes after glucose loading [11]. Moreover, a study using CGM including FGM for type 1 diabetes patients indicated that all sensors performed less accurately during hypoglycemia and best during hyperglycemia [12]. These observations strongly suggest that values obtained from FGM should be examined in a clinical context.…”
Section: Disclosurementioning
confidence: 95%